ANALISIS HUKUM TERHADAP KEWENANGAN MAJELIS PENGAWAS WILAYAH DALAM PENERAPAN SANKSI ATAS PELANGGARAN ADMINISTRASI YANG DILAKUKAN NOTARIS DITINJAU DARI UNDANG-UNDANG NOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS - ANDRE PRIMA SEMBIRING (PREMISE LAW JURNAL, 2016)
ABSTRACT The administrative sanction imposed on the notary who breaks the law by the Regional Supervisory Council are written and oral warnings and should use the strong principles, such as the council that imposes the sanctions should be competent in law and notary, and mechanisms of sanction imposition are based on the valid systems in Indonesia, and support the justice values and legal certainty. The sanction imposition should have legal efforts taken by the parties to guarantee legal certainty to look for legal justice The Regional Supervisory Council, in this case, becomes the instrument to enforce the laws in the scope of Notary Law should be fair and independent supported by the government. Keywords: Regional Supervisory Council, Administrative Sanction